2022
DOI: 10.3390/ijms23116296
|View full text |Cite
|
Sign up to set email alerts
|

Notch Signaling in Breast Tumor Microenvironment as Mediator of Drug Resistance

Abstract: Notch signaling dysregulation encourages breast cancer progression through different mechanisms such as stem cell maintenance, cell proliferation and migration/invasion. Furthermore, Notch is a crucial driver regulating juxtracrine and paracrine communications between tumor and stroma. The complex interplay between the abnormal Notch pathway orchestrating the activation of other signals and cellular heterogeneity contribute towards remodeling of the tumor microenvironment. These changes, together with tumor ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 140 publications
0
11
0
Order By: Relevance
“…It has been discovered that Notch-3 NICD is abundantly expressed in breast tissue and is linked to the prevalence of mammary gland tumors, revealing its potential as an oncogene. Several breast gland cell lines associated with breast cancer have also been shown to express Notch-1 and Notch-3 NICD, supporting the idea of their involvement in breast tumorigenesis 142 . Dysfunctional genetic variants of Notch-4 NICD have been linked to breast tumorigenesis as well.…”
Section: Clinical Investigation Into Notch Signalling Expressionmentioning
confidence: 60%
“…It has been discovered that Notch-3 NICD is abundantly expressed in breast tissue and is linked to the prevalence of mammary gland tumors, revealing its potential as an oncogene. Several breast gland cell lines associated with breast cancer have also been shown to express Notch-1 and Notch-3 NICD, supporting the idea of their involvement in breast tumorigenesis 142 . Dysfunctional genetic variants of Notch-4 NICD have been linked to breast tumorigenesis as well.…”
Section: Clinical Investigation Into Notch Signalling Expressionmentioning
confidence: 60%
“…In the cell–cell interactions analysis, we found JAG-NOTCH interactions between tumor cells and endothelial cells. The Notch pathway is involved in tumor progression through various mechanisms such as stem cell maintenance, cell proliferation, and migration/invasion [ 51 , 52 ]. These studies reported that the Notch pathway regulates many components of the TME, including immune cells, fibroblast, endothelial, and mesenchymal cells.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the high expression of the HER2 gene renders cancer cells more resistant to cisplatin treatment in some tumors [ 8 ]. Furthermore, it may depend on the heterogeneity of tumors in which the existence of specific subpopulations in tumors such as CSCs with self-renewal and differentiation capacity participate in both tumor progression and resistance to chemotherapy drugs in different types of cancer [ 7 , 9 ]; the activation of intrinsic pathways used as a defense against environmental toxins (such as anti-cancer drugs) predisposes to chemoresistance. On the other hand, the acquired resistance after treatment, resulting from new proto-oncogenes activation, mutations or altered expression levels of specific drug targets, as well as changes in the tumor microenvironment, has been reported [ 7 , 9 ].…”
Section: Introductionmentioning
confidence: 99%